Formant Analysis in Native and Non-Native Speakers - Syarfina, Tengku; Siregar, Maysarah (Fakultas Tarbiyah IAI Nasional Laa Rooiba, 2024)
This research wants to find out how the voice formants of people who speak English as their first language differ from the voices of people who speak English as a second language. This research uses a computer program called Praat to help with the research. The people to be studied are those who grew up speaking English and those who learned it later in life. The samples in this research were taken 1 male voice and 1 female voice non-native speaker and 2 native speaker voice sample Male and Female. The findings of the analysis show that there are not many differences between native and non-native speakers' pronunciations of each monophthong, especially when they relate to the monophthong /ə/, which is difficult for non-native speakers to pronounce correctly.